Evaluation of Haller's Cells Prevalence in a Sample of Polish Population Assessed Using Panoramic Radiographs - Angelika Manaj; Aleksandra Osiak; Magdalena Piskórz; Karolina Futyma-Gąbka; Ingrid Różyło-Kalinowska (Indian Journal of Medical Specialities)
Introduction: Haller's cells are air structures with variable presence in individuals. They are situated in the anterior part of the ethmoid bone on the inferior and medial walls of the orbits. Their presence can be symptomatic and they may also be an impediment in surgical procedures. A panoramic radiograph commonly used in dental diagnostics allows visualization of their presence. The aim of the study is characteristics and estimation of Haller's cell prevalence in a sample of the Polish population based on panoramic radiographs. Materials and Methods: The study consisted of 467 panoramic radiographs including patients of both genders (303 females and 164 males), aged 17–23 years with a mean of 20.2 years. All radiographs have been evaluated for Haller's cells' presence, shape, number, and location with gender predilection. Results: Haller's cells were found in 72 cases, which comprised 15.4% of the studied group, with a slightly higher prevalence in females (17.82% in females and 10.97% in males). The most predominant shape was oval. Unilateral distribution of the cells outnumbered bilateral variants. One to three Haller's cells were found on one side, in the own material. Conclusions: Panoramic radiograph revealed a relatively low prevalence of Haller's cells in a sample of the Polish population. It is possible to assess the shape and determine the exact number of these cells. Based on the panoramic examination, we can state that they are located more often unilaterally with a slightly higher prevalence in females.